Differential influence of molybdenum and tungsten on the growth of barley seedlings and the activity of aldehyde oxidase under salinity - Batyrshina, Zhaniya (Journal of plant physiology, 2018)
Copyright © 2018 Elsevier GmbH. All rights reserved.